2021
DOI: 10.1177/23294884211019098
|View full text |Cite
|
Sign up to set email alerts
|

The Project Communication and Trust Nexus as an Antecedents of Project Success: Moderating Role of Authentic Leadership

Abstract: The present study aims to investigate the impact of project communication on project success with the mediating role of trust and the moderating role of authentic leadership. The sample is drawn using a convenient sampling technique. The data is collected through the online survey method due to the COVID-19 pandemic, from project-based construction companies of Pakistan ( n = 245). The analyses are established using SPSS v.25 and AMOS v.23 software to test hypotheses. The results indicate that project communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The articles included in this SLR demonstrate a significant and positive relationship between communication and PS [15,72,77,78], in agreement with previous research findings [93,94]. The significance of this competence lies in its impact throughout various stages of a project [94].…”
Section: Discussionsupporting
confidence: 85%
“…The articles included in this SLR demonstrate a significant and positive relationship between communication and PS [15,72,77,78], in agreement with previous research findings [93,94]. The significance of this competence lies in its impact throughout various stages of a project [94].…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, while the combined impact of all variables is still being studied, it was found that the construction project's success is related to (22.0% and 26.5%) communication management. These results strongly support the second hypothesis (H 2 ), i.e., that a construction project's success is positively impacted by effective communication management, according to research that is consistent with studies of references [169,170]. According to the global context, the communication gap is a challenge for project success [171].…”
Section: Discussionsupporting
confidence: 83%
“…Quanto ao papel ativo das pessoas em papel de gestão de projetos no desenvolvimento da confiança da equipe de projetos, existe uma relação positiva quando há uma certa clareza e confiança entre os membros e a pessoa no papel de gestão pois o papel moderador da liderança fortalece a relação entre a comunicação do projeto e a confiança (Majeed;Kayani;Haider, 2021;Parker;Kunde;Zeppetella, 2017;Wang et al, 2022). Por esse motivo, é necessário ter vários graus de confiança nessa relação, visto que a confiança total e incontestável, invariavelmente, leva a um pensamento de grupo que dificulta a tomada de decisões críticas em um ambiente de projetos.…”
Section: Análise E Discussãounclassified